Pharmacokinetics of a Long-Acting Formulation of Oxytetracycline in Freshwater Crocodiles (Crocodylus siamensis) after Intramuscular Administration at Three Different Dosages - Saranya Poapolathep; Narumol Klangkaew; Napasorn Phaochoosak; Tara Wongwaipairoj; Mario Giorgi; Narongsak Chaiyabutr; Darren J. Trott; Amnart Poapolathep (Animals, 2020)
To date, the necessary pharmacokinetic information has been limited to establish suitable therapeutic plans for freshwater crocodiles. Therefore, this study was conducted to evaluate the pharmacokinetic profile of the oxytetracycline long-acting formulation (OTC-LA) in the freshwater crocodile, Crocodylus siamensis, following a single intramuscular (i.m.) administration at three different dosages of 5, 10 and 20 mg/kg body weight (b.w.). Blood samples were collected at assigned times up to 216 h after i.m. administration at the three different dosages. The plasma concentrations of OTC were measured using a validated liquid chromatography tandem-mass spectrometry (LC-MS/MS) method. The Cmax (± SD) values of OTC were 2.15 ± 0.51 µg/mL, 7.68 ± 1.08 µg/mL and 17.08 ± 2.09 µg/mL at doses of 5, 10 and 20 mg/kg b.w., respectively. The elimination half-life values were 33.59 ± 2.51 h, 38.42 ± 5.47 h and 38.04 ± 1.98 h at dosages of 5, 10 and 20 mg/kg b.w., respectively. Based on the pharmacokinetic data, the pharmacokinetic/pharmacodynamic (PK/PD) index, the susceptibility break-point and plasma protein binding, a dosage once every two weeks of 10 mg/kg b.w. OTC intramuscularly might be suitable for initiating the treatment of susceptible bacterial infections in freshwater crocodiles. However, further PK/PD studies are warranted to confirm whether the dose rates used in this study can produce longer-term antimicrobial success for diseases caused by susceptible bacteria in freshwater crocodiles.